Gradient observability and sensors for hyperbolic systems (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
The aim of this paper is to develop useful rigorous results related tothe gradient observability and sensors. The concept of gradient strategic sensors is characterized and applied to the wave equation. This emphasizes the spatial structure and location of the sensors in order that regional gradient observability can be achieved. The developedÂ  results are illustrated by many examples, Finally The reconstruct method leads to a numerical algorithm illustrated by simulations.